2011
DOI: 10.3892/ijmm.2011.735
|View full text |Cite
|
Sign up to set email alerts
|

Inability of NCoR/SMRT to repress androgen receptor transcriptional activity in prostate cancer cell lines

Abstract: Abstract. The molecular mechanisms leading to castrationresistant prostate cancer (CRPC) are poorly understood. Among several mechanisms leading to CRPC growth a dysregulation of androgen receptor (AR) co-regulators (i.e. up-regulation of co-activators or down-regulation of co-repressors) is discussed. There are numerous reports demonstrating an increased expression of co-activators during prostate cancer progression. On the contrary, the impact of co-repressors on tumor growth and development is less clear. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Our data indicate that this effect can be prevented by the presence of nuclear FlnA but further studies are needed to elucidate the mechanism by which FlnA promotes this effect. In this respect, FlnA is distinct from other AR co-repressors such as NCoR and SMRT and likely explains results showing the inability of the latter to inhibit AR activity in CRPC lines (Laschak, et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that this effect can be prevented by the presence of nuclear FlnA but further studies are needed to elucidate the mechanism by which FlnA promotes this effect. In this respect, FlnA is distinct from other AR co-repressors such as NCoR and SMRT and likely explains results showing the inability of the latter to inhibit AR activity in CRPC lines (Laschak, et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…DU-145 and PC-3 cells were grown in 24-well plates and co-transfected with 150 ng/well of pFN10A-AR, pFN11A-AR and the Gal4 reporter construct pGL4.31. After transfection, cells were cultured and luciferase activities were determined as recently described [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Although this would usually favour AR transcriptional inactivation, the situation may be different in a particular cellular context; exogenous overexpression of NCOR1 and NCOR2 can increase AR transcriptional activity, possibly due to an impaired AR/co-repressor interaction [81]. Another study found altered recruitment to AR but also loss of expression of NCOR1/2 in CWR22R castration-resistant cells compared to the androgen-dependent CWR22 [82].…”
Section: Co-regulator Alterations and Aberrant Transcriptionmentioning
confidence: 99%